2006
DOI: 10.1124/mol.106.022376
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-Selective Mechanisms of μ-Opioid Receptor Desensitization in Human Embryonic Kidney 293 Cells

Abstract: The ability of two opioid agonists, [D-Ala 2 ,N-Me-Phe 4 ,Gly 5 -ol]-enkephalin (DAMGO) and morphine, to induce -opioid receptor (MOR) phosphorylation, desensitization, and internalization was examined in human embryonic kidney (HEK) 293 cells expressing rat MOR1 as well G protein-coupled inwardly rectifying potassium channel (GIRK) channel subunits. Both DAMGO and morphine activated GIRK currents, but the maximum response to DAMGO was greater than that of morphine, indicating that morphine is a partial agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
179
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(206 citation statements)
references
References 41 publications
20
179
0
7
Order By: Relevance
“…These findings indicate that morphine elicits desensitization without an apparent change in the number of MOR. This is in agreement with previous studies, which found that morphineinduced desensitization took place without ␤-arrestin-mediated MOR internalization (Johnson et al, 2006;Groer et al, 2007). Most relevantly, it was demonstrated that the initial exposure to morphine causes G␣ depletion due to the interaction of G␣ with RGS, while further exposure to morphine elicits phosphorylation and internalization of MOR (Rodríguez-Muñoz et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings indicate that morphine elicits desensitization without an apparent change in the number of MOR. This is in agreement with previous studies, which found that morphineinduced desensitization took place without ␤-arrestin-mediated MOR internalization (Johnson et al, 2006;Groer et al, 2007). Most relevantly, it was demonstrated that the initial exposure to morphine causes G␣ depletion due to the interaction of G␣ with RGS, while further exposure to morphine elicits phosphorylation and internalization of MOR (Rodríguez-Muñoz et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
“…While the molecular mechanisms underlying the development of opioid-induced tolerance have not been fully clarified, desensitization appears to contribute to tolerance. Morphine desensitizes the receptor via a protein kinase C (PKC)-dependent pathway (Johnson et al, 2006), while a synthetic opioid agonist desensitizes MOR -opioid receptor by G-protein-coupled receptor kinase (GRK) dependent internalization and the resultant downregulation of MOR expression (Zhang et al, 1998). Regulator of G-protein signaling (RGS) proteins were identified as taking part in the receptor's desensitization independent of its internalization and downregulation (Garzó n et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to GRK-␤arr dependent mechanisms, protein kinase C (PKC) and ERK1/2 activation can mediate or enhance MOR desensitization in heterologous expression systems (Schmidt et al, 2000;Bohn et al, 2002;Johnson et al, 2006). Together, these observations suggest either that MOR desensitization under different experimental conditions can occur via different molecular mechanisms Johnson et al, 2006) or, alternatively, MOR desensitization is mediated by multiple mechanisms in native neurons.…”
Section: Introductionmentioning
confidence: 86%
“…Together, these observations suggest either that MOR desensitization under different experimental conditions can occur via different molecular mechanisms Johnson et al, 2006) or, alternatively, MOR desensitization is mediated by multiple mechanisms in native neurons. To determine whether MOR desensitization is mediated by multiple molecular mechanisms, this study used patch-clamp recordings of the activation of GIRK channels by MOR in brain slices containing LC neurons from ␤arr-2 wild type (w.t.)…”
Section: Introductionmentioning
confidence: 96%
“…The hyperpolarization produced by high concentrations of morphine or DAMGO appeared to wane over time, and when the cells were challenged with a concentration of agonist that should saturate the cell surface receptors, there was a marked decrease in this response after only a few minutes of exposure to the agonist, consistent with analogous studies performed in locus coeruleus neurons 27 or cell lines transfected with µ-opioid receptors and GIRK channels. 28 We were able to make use of the endogenous sst receptors in the AtT-20 cells to determine whether exposure to desensitizing concentrations of opioid agonist affected signaling through other receptors. The time constant for the desensitization of signaling produced by morphine was slower than that reported in our previous study of opioid signaling, which used inhibition of I Ca in AtT-20 cells, and this may reflect a distinct recruitment of desensitization processes by morphine in intact cells compared with cells dialyzed by patch-clamp recording.…”
Section: Discussionmentioning
confidence: 99%